The determinant of export performance of Perodua in United Kingdom / Nurul Izzah Abdullah (Faculty of Business and Management, 2007)
This study was conducted to examine the determinants export performance of Perodua in United Kingdom (UK). The objective was to study the trend of export performance of Perodua in UK from year 1997 to year 2006. Other than that, this research study was also to identify the major factors that affect export performance of Perodua in UK. To meet the objectives, the researcher used two methods of study. For trend analysis, the researcher wanted to figure out the fluctuation to the sales volumes of Perodua in UK. In addition for the major factors that affected the export performance, the researcher used the Statistical Package Social Science (SPSS) software in order to analyze and understand which factors that influence export performance. At the end of the research, based from the findings several recommendations have been made to the firm and also for future research purposes.